СПОРТИВНИЙ ТУРИЗМ ЯК ЗАСІБ ФІЗИЧНОГО ВИХОВАННЯ СТУДЕНТСЬКОЇ МОЛОДІ (Педагогіка вищої та середньої школи, 2008)
In this article it is necessity and efficiency of the use of sporting tourism as facilities of physical education of students. A purpose and functions of sporting tourism open up. The detailed analysis of scientifically-methodical principles of successful realization of educational and training process is done in the system of physical education.